Apparent Viscosity Direct from Marsh Funnel Test - H. M. Almahdawi, Faleh; Zarzor Al-Yaseri, Ahmed; Jasim, Nagham (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Accurate and simple techniques for measurement of fluid rheological properties are important for field operations in the oil industry. Marsh Funnels are popular quality-control tools used in the field for drilling fluids and they offer a simple, practical alternative to viscosity measurement. In the normal measurements, a single point (drainage time) is used to determine an average viscosity; little additional information is extracted regarding the non-Newtonian behavior of the fluid.Here, a new model is developed and used to determine the rheological properties of drilling muds and other non-Newtonian fluids using data of fluid density and drainage time collected from a Marsh Funnel as a function of viscosity. The funnel results for viscosity compare favorably to the values obtained from a commonly-used Fann 35 viscometer. Different quantities of bentonite, barite and other additives which have been used to prepare many samples. Empirical equations are obtainedμapp. = ρ (t – 28) and μapp. = -0.0118t2 + 1.6175t - 32.168,where apparent viscosity (μapp.) in (cp), Marsh funnel time (t) in seconds and the density (ρ) in gm/cm3.